2021
DOI: 10.1074/jbc.ra120.014126
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferase ST6Gal-I promotes the epithelial to mesenchymal transition in pancreatic cancer cells

Abstract: ST6Gal-I, an enzyme upregulated in numerous malignancies, adds α2-6-linked sialic acids to select membrane receptors, thereby modulating receptor signaling and cell phenotype. In this study, we investigated ST6Gal-I’s role in epithelial to mesenchymal transition (EMT) using the Suit2 pancreatic cancer cell line, which has low endogenous ST6Gal-I and limited metastatic potential, along with two metastatic Suit2-derived subclones, S2-013 and S2-LM7AA, which have upregulated ST6Gal-I. RNA-Seq results suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 52 publications
7
57
0
Order By: Relevance
“…In line with our sc-RNAseq analysis, staining for ST6GAL1 protein was strongest in epithelial cells, suggesting that ductal or acinar specific expression may significantly contribute to development and/or progression of PDA. Consistent with our observations in patients and the KC mouse model, in vitro cell culture models of pancreatic cancer with ST6GAL1 overexpressed promoted chemo-resistance, cell growth and a stem-cell like phenotype (7,8,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with our sc-RNAseq analysis, staining for ST6GAL1 protein was strongest in epithelial cells, suggesting that ductal or acinar specific expression may significantly contribute to development and/or progression of PDA. Consistent with our observations in patients and the KC mouse model, in vitro cell culture models of pancreatic cancer with ST6GAL1 overexpressed promoted chemo-resistance, cell growth and a stem-cell like phenotype (7,8,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 90%
“…In ST6KC, we observed significant protection against formation of PanIn lesions, an early step in malignant transformation, and reduction of fibrosis, which is associated with immune suppression and resistance to treatment in PDAC patients (33). This is consistent with the function of ST6GAL1 in cell studies (7,8,(30)(31)(32). Overall, histological assessment of our ST6KC mice demonstrates a clear protective role for genetic deletion of ST6GAL1 in PDA.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In pancreatic cancer cells, high expression of ST6GAL1 led to increased α-2,6 sialylation and activation of EGFR, as well as upregulation of mesenchymal markers and enhanced cell invasiveness. Interestingly, the EGFR inhibitor erlotinib attenuated the ST6GAL1-dependent differences in EGFR sialylation and activation, EMT marker expression and invasiveness [ 66 ]. In addition, increase of α-2,3 sialylation induced by ST6GAL1 promoted integrin α5β1-dependent adhesion in hepatocarcinoma cells [ 67 ].…”
Section: Roles Of Sialyltransferases In Cancermentioning
confidence: 99%
“…Sialidase-treated A549 cells were less sensitive to EGF-stimulated cell proliferation than A549 cells without sialidase treatment, and the TKI erlotinib showed no significant effects upon sialidase treatment [ 51 ]. Britain et al [ 52 ] found that high expression levels of α2,6-sialyltransferase ST6Gal I that acts on complex N -glycans of EGFR correlates with EGF-triggered EGFR activation in pancreatic cancer cells [ 52 , 53 ]. The high expression of ST6Gal I also resulted in gefitinib resistance.…”
Section: Tyrosine Kinase Receptorsmentioning
confidence: 99%